Alterations in Antioxidant Potentials of Synechococcus Spp. Exposed to Hexazinone toxicity - Singh, Santosh Kumar; Verma, Satish Kumar; Siddiqui, Md. Aslam; Singh, Devendra; Sharma, Brij Mohan (Indian Forester, 2012)
Cyanobacteria are a group of diverse Gram-negative organisms that are one of the most primitive photosynthesizes. Attention is drawn towards the alterations in physlogical chances in cyanobacteria exposed to pesticides stress. Synechococcus cultures were exposed to various concentration of the herbicide hexazinone and the tolerant cyanobacteria were used to study the alterations in antioxidant activities, growth and lipid peroxidation levels. All parameters showed a high degree of susceptibility towards high doses of hexazinone. Recovered cyanobacteria showed lower MDA content and super oxide and peroxide radicals. The present findings suggested that high concentration of Hexazinone might modulate the antioxidative system of Synechococcus spp. A significant conclusion can be drawn from the findings that improved tolerance to herbicide stress may be accomplished by increased capacity of antioxidant system of cyanobacteria.